Atrial Dyssynchrony and Bachmann Bundle Pacing: A Review. - Kim,JU; Kaza,N; Zuhair,M; Naraen,A; Arnold,AD; Shun-Shin,MJ; Francis,DP; Vernooy,K; Luermans,JGLM; Israel,C; Whinnett,ZI; Keene,D (JAMA Cardiol, 2026)
IMPORTANCE: Cardiac dyssynchrony disrupts coordinated chamber activation and is associated with impaired cardiac function and adverse clinical outcomes. While ventricular dyssynchrony has been targeted through biventricular and conduction system pacing, atrial dyssynchrony remains underrecognized and largely untreated. OBSERVATIONS: Interatrial dyssynchrony commonly arises from delayed or impaired conduction through Bachmann bundle or from nonphysiological atrial pacing. It is associated with impaired ventricular filling and increased atrial arrhythmia risk. Importantly, conventional atrial pacing strategies may exacerbate rather than correct abnormal atrial activation. Bachmann bundle pacing represents a potential strategy to restore physiological atrial activation by engaging the dominant interatrial conduction pathway. Emerging data suggest that this approach may improve atrial synchrony, optimize atrioventricular timing, and reduce arrhythmia burden. CONCLUSIONS AND RELEVANCE: In this review, we summarize the mechanisms and clinical consequences of interatrial dyssynchrony and evaluate the role of Bachmann bundle pacing as a novel target for atrial resynchronization and a potential next step in physiological pacing. Further studies are required to define optimal implantation strategies and determine Bachmann bundle pacing's clinical impact.